2013
DOI: 10.1155/2013/709145
|View full text |Cite
|
Sign up to set email alerts
|

Immunocytochemical Characterization of Alzheimer Disease Hallmarks in APP/PS1 Transgenic Mice Treated with a New Anti-Amyloid-βVaccine

Abstract: APP/PS1 double-transgenic mouse models of Alzheimer's disease (AD), which overexpress mutated forms of the gene for human amyloid precursor protein (APP) and presenilin 1 (PS1), have provided robust neuropathological hallmarks of AD-like pattern at early ages. This study characterizes immunocytochemical patterns of AD mouse brain as a model for human AD treated with the EB101 vaccine. In this novel vaccine, a new approach has been taken to circumvent past failures by judiciously selecting an adjuvant consistin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 65 publications
1
9
0
Order By: Relevance
“…84,85 Although the scope of this review is on liposome-strategies with the aim of facilitating BBB crossing, it is important to mention that other strategies have been developed for the use of liposomes for AD treatment. 89,[113][114][115][116] Curcumin is a natural compound extract from the plant Curcuma longa, and has been reported to be a fluorescent molecule with high affinity for the Aβ peptide and able to reduce Aβ aggregation. In this way, intracranial injection of liposomes encapsulating curcumin efficiently labeled Aβ deposits in both human and mice tissues, proving to be an effective formulation for diagnosis and treatment of AD.…”
Section: Data Extractionmentioning
confidence: 99%
See 1 more Smart Citation
“…84,85 Although the scope of this review is on liposome-strategies with the aim of facilitating BBB crossing, it is important to mention that other strategies have been developed for the use of liposomes for AD treatment. 89,[113][114][115][116] Curcumin is a natural compound extract from the plant Curcuma longa, and has been reported to be a fluorescent molecule with high affinity for the Aβ peptide and able to reduce Aβ aggregation. In this way, intracranial injection of liposomes encapsulating curcumin efficiently labeled Aβ deposits in both human and mice tissues, proving to be an effective formulation for diagnosis and treatment of AD.…”
Section: Data Extractionmentioning
confidence: 99%
“…113 Also, intraperitoneal injection of liposomes containing phosphatidic acid or cardiolipin was able to reduce Aβ peptides in the plasma and shifted the equilibrium that exists between brain and blood Aβ peptides, slightly affecting the plaques in the brain. 89 Lastly, different liposome-based vaccines were developed and directed toward Aβ plaques 115,116 and tau.…”
Section: Data Extractionmentioning
confidence: 99%
“…Among these, APP/PS1 double transgenic mice are an extensively used model, showing progressive age-related development of Aβ accumulation and cognitive deficits (Jankowsky et al 2001;Trinchese et al 2004;van Groen et al 2006;Meyer-Luehmann et al 2009;Filali et al 2011;Janus et al 2015). Furthermore, previous studies have revealed positive results, such as demonstrating various antioxidants (Garcia-Alloza et al 2010;Varamini et al 2014;Yanagisawa et al 2015), neuroprotective agents (Kilgore et al 2010;Peng et al 2012;Li et al 2014), anti-neuroinflammation (Cherry et al 2015;Guo et al 2015), immune therapy (Sudduth et al 2013;Carrera et al 2013;Zhang et al 2015), and nonpharmacological interventions (Liu et al 2011;Jankowsky et al 2005), which can attenuate or even reserve AD-like pathology in APP/PS1 mice. Unfortunately, none of these potentially useful results have been able to be reproduced in clinical therapies for AD patients.…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical trial had to be interrupted because of a significant number of meningoencephalitis among the immunized subjects probably induced by an extensive T-cell-mediated immune response [202]. In order to overcome this problem, Carrera et al developed a system (EB101) consisting of A 1−42 and sphingosine-1-phosphate emulsified in a phospholipid liposome complex [203][204][205]. Monthly intraperitoneal administration (9 injections, 7 months) of EB101 to APP/PS1 mice before the onset of A deposition and/or at an older age was effective in halting the progression and reducing the AD-like neuropathological hallmarks: A plaques, neurofibrillary tangle-like structures, activated astrocytes, and neuroinflammation.…”
Section: Anti-aβ Vaccinementioning
confidence: 99%